VISUAL NARRATIVES IN ADVERTISING WOMEN-CENTRIC GOVERNMENT SCHEMES AND THEIR IMPACT ON RURAL WOMEN - Prasad, Deepak; Mishra, Pranav; Kumar, Vikash; Sharma, Monika; Choudhary, Rama; Suman, Shobhit (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The schemes that are women-focused are crucial in promoting the gender equality and social inclusion and economic empowerment, especially to the women who are in the rural areas. Nevertheless, the success of these schemes is not only based on the way they are designed but relies also on their efficiency in the communication to the beneficiaries. In this regard, the visual narratives applied to government advertisement can be viewed as the critical link between the purpose of the policy and the grassroots initiatives. This paper explores the importance of the visual narratives in the advertisement of women-based government programs and assesses how it affects the awareness, perception and behavioral intention of rural women. The research design will be that of a mixed method study, that is, a quantitative content analysis of a sample of government advertisements and a survey-based measurement of the impact of the same to the rural women. The analysis of visual narratives has been done on the dimensions that include narrative structure, women-representation, symbolism, emotional appeal, and consistency of the message. In order to measure narrative strength, a Visual Narrative Effectiveness Index (VNEI) was created. The impact assessment involved the testing of the effect of these visual strategies on levels of awareness, trust, perceived relevance and perceptions of intention to participate in government schemes. The results show that transformation-based storytelling, empowered but culturally based portrayal of rural women, emotional appeals, especially hope and security, characterize government ads. The score of VNEI was high, which means narrative effectiveness on all dimensions. Empirical findings also indicate that visual narratives substantially enhance awareness and positive perception in rural women particularly those with low levels of formal education and high dependency on media of visual literacy. Although visual advertising is extremely persuasive to behavioral intention, procedural and socio-cultural barriers mediate actual participation, which shows an intention action gap. The research is relevant to the literature on visual communication, gender-based advertising and communication of public policy due to the ability to quantify a scheme of evaluating visual narratives. In real world terms, it can provide policy makers and communication companies with practical insights on how to create culturally sensitive, emotionally sensitive, and inclusive advertising campaigns to strengthen the effectiveness of women-based government programs in rural areas.